STUDI ANALISIS RESPONSIBILITAS DAN KAUSALITAS GRANGER PRODUKTIFITAS TEMBAKAU TERHADAP PRODUK DOMESTIK REGIONAL BRUTO JEMBER TAHUN 2011-2014 - Fitri Rusdianasari; Ida Alqurnia (UPT Penerbitan Universitas Jember)
The use of tobacco plant as a symbol of the area as well as batik motif typical of the area showed that tobacco plants also a local wisdom in Jember. But the last 4 years, productivity of tobacco has decreased, while economic growth in Jember steadily growing over the last 4 years. Therefore we draw two formulation of the problem is how the productivity elasticity of tobacco in Jember? and how the relationship with productivity GRDP Jember tobacco? Are there long-term relationship. From the test results we found that the elasticity of productivity tobacco has the same elasticity is inelastic, while Granger kausality test results showed that in both variables affect each other there is no relationship, but only variables that affect GRDP is productivity Tobacco.